Enhanced delivery of PEAL nanoparticles with ultrasound targeted microbubble destruction mediated siRNA transfection in human MCF-7/S and MCF-7/ADR cells in vitro - Teng Y (Dove Medical Press, 2015)
Yanwei Teng,1,2,* Min Bai,3,* Ying Sun,2 Qi Wang,1,2 Fan Li,3 Jinfang Xing,3 Lianfang Du,3 Tao Gong,1 Yourong Duan2 1Key Laboratory of Drug Targeting and Novel Drug Delivery Systems, Ministry of Education, West China School of Pharmacy, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2State Key Laboratory of Oncogenes and Related Genes, Shanghai Cancer Institute, Renji Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai, People’s Republic of China; 3Department of Ultrasound, Shanghai First People’s Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: The gene knockdown activity of small interfering RNA (siRNA) has led to their use as potential therapeutics for a variety of diseases. However, successful gene therapy requires safe and efficient delivery systems. In this study, we choose mPEG-PLGA-PLL nanoparticles (PEAL NPs) with ultrasound targeted microbubble destruction (UTMD) to efficiently deliver siRNA into cells. An emulsification-solvent evaporation method was used to prepare siRNA-loaded PEAL NPs. The NPs possessed an average size of 132.6±10.3 nm (n=5), with a uniform spherical shape, and had an encapsulation efficiency (EE) of more than 98%. As demonstrated by MTT assay, neither PEAL NPs nor siRNA-loaded PEAL NPs showed cytotoxicity even at high concentrations. The results of cellular uptake showed, with the assistance of UTMD, the siRNA-loaded PEAL NPs can be effectively internalized and can subsequently release siRNA in cells. Taken together, PEAL NPs with UTMD may be highly promising for siRNA delivery, making it possible to fully exploit the potential of siRNA-based therapeutics. Keywords: gene delivery, mPEG-PLGA-PLL, UTMD, emulsification-solvent evaporation method, orthogonal design